Non‐3d Metal Modulation of a Cobalt Imidazolate Framework for Excellent Electrocatalytic Oxygen Evolution in Neutral Media - Xu, Yan‐Tong; Ye, Zi‐Ming; Ye, Jia‐Wen; Cao, Li‐Ming; Huang, Rui‐Kang; Wu, Jun‐Xi; Zhou, Dong‐Dong; Zhang, Xue‐Feng; He, Chun‐Ting; Zhang, Jie‐Peng; Chen, Xiao‐Ming (Angewandte Chemie International Edition, 2019)
Cobalt imidazolate frameworks are classical electrocatalysts for the oxygen evolution reaction (OER) but suffer from the relatively low activity. Here, a non‐3d metal modulation strategy is presented for enhancing the OER activity of cobalt imidazolate frameworks. Two isomorphous frameworks [Co4(MO4)(eim)6] (M=Mo or W, Heim=2‐ethylimidazole) having Co(eim)3(MO4) units and high water stabilities were designed and synthesized. In different neutral media, the Mo‐modulated framework coated on a glassy carbon electrode shows the best OER performances (1 mA cm−2 at an overpotential of 210 mV in CO2‐saturated 0.5 m KHCO3 electrolyte and 2/10/22 mA cm−2 at overpotential of 388/490/570 mV in phosphate buffer solution) among non‐precious metal catalysts and even outperforms RuO2. Spectroscopic measurements and computational simulations revealed that the non‐3d metals modulate the electronic structure of Co for optimum reactant/product adsorption and tailor the energy of rate‐determining step to a more moderate value. Non‐3D for 3D: Introducing non‐3d metal oxide units into a cobalt imidazolate framework results in the drastic enhancement of electrocatalytic performance of the oxygen evolution reaction in neutral media.